A novel method for damage analysis of CFRP single-lap bolted, bonded and hybrid joints under compression. (1st November 2020) - Zhang, Hongzhuang; Li, Changyou; Xu, Mengtao; Liu, Zhendong; Jia, Dawei; Zhang, Yimin
Abstract: The purpose of this paper is to investigate the failure mechanisms of carbon fiber reinforced composites (CFRP) single-lap bolted, bonded and hybrid bolted/bonded joints during compression. The failure process and the failure mechanisms of the compression tests were analyzed using field emission scanning electron microscope (FESEM) and acoustic emission (AE) technique. A novel method is proposed to obtain the relationship between the FESEM analysis and AE signals. The crack data is obtained by identifying, segmenting and quantizing FESEM images based on image processing technology. The final results give effective AE parameters for identifying crack damage in composite joints, and show the superiority of the proposed method. The research in this paper puts forward important suggestions for the application of AE technique in composites and fault diagnosis.